2015
DOI: 10.15171/ijhpm.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health needs of HIV-positive people in Tehran, Iran: a mixed-method descriptive study

Abstract: Background: People Living with HIV (PLHIV) are highly stigmatized and consequently hard-to-access by researchers and importantly, public health outreach in Iran, possibly due to the existing socio-cultural situation in this country. The present study aimed to evaluate the sexual and reproductive health needs of PLHIV in Tehran, the capital of Iran. Methods: As a mixed-method descriptive study, this project was conducted in 2012 in Tehran, Iran. In this study, we evaluated and discussed socio-demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 16 publications
5
59
0
Order By: Relevance
“…The trend of the use of contraceptive before and after HIV diagnosis suggest tremendous increase in the use of condom compared to non-condom contraceptives. This finding is supported by the research done in the Kathmandu district of Nepal, Iran, Swaziland, India and Uganda (4, 22,23,28,29). According to the mixed method study done on Iran the people living with HIV were not willing to use other than condom because of the recommendation made by the health care providers as the main method of contraception (28).…”
Section: Utilization Of the Family Planning Methodsmentioning
confidence: 75%
“…The trend of the use of contraceptive before and after HIV diagnosis suggest tremendous increase in the use of condom compared to non-condom contraceptives. This finding is supported by the research done in the Kathmandu district of Nepal, Iran, Swaziland, India and Uganda (4, 22,23,28,29). According to the mixed method study done on Iran the people living with HIV were not willing to use other than condom because of the recommendation made by the health care providers as the main method of contraception (28).…”
Section: Utilization Of the Family Planning Methodsmentioning
confidence: 75%
“…In this study, 60 individuals (15%) reported "intention to pregnancy" as their main reason for not using a condom. However, evidence suggest that most of the sexual and reproductive health needs of Iranian PLWHA have been overlooked by the health policy makers in this country (20). Therefore, development and enhancement of the relevant services such as treatment, care, support, as well as pre-and post-delivery counseling seems necessary to prevent mother to child transmission of HIV (PMTCT) in the community.…”
Section: Discussionmentioning
confidence: 99%
“…The present results come from the quantitative section of a mixed-method study evaluating the sexual life of Iranian PLWHA. Results of the qualitative section appear elsewhere (20). Condom use was considered as consistent, when the respondents reported "always" using a condom in the past year.…”
Section: Design and Settingmentioning
confidence: 99%
“…Sample sizes ranged from 10 to 881 WLHIV who were interviewed or completed an individual questionnaire in a hospital (69.2%) or in a community-support group context. The authors of five papers (38.5%) reported on studies conducted in Iran [41,42,48,49,51], and five studies included an exploration of the SRH of men living with HIV [40,44,47,48,50].…”
Section: Characteristic Of Studiesmentioning
confidence: 99%